PENGARUH KONSENTRASI ZAT PENGATUR TUMBUH ATONIK PADA DUA VARIETAS TANAMAN JAHE (Zingiber officinale) PADA PERTUMBUHAN FASE VEGETATIF - Ardito Risano; Sutini Sutini; Didik Utomo Pribadi (UPN VETERAN JAWA TIMUR, 2023)
The ginger plant (Zingiber officinale) is one of the plant commodities included in the Zingiberaceae family known as ginger. The ginger plant was the most popular spice and was used by Europeans in antiquity. Apart from being an herbal plant, the ginger plant stores antioxidant substances that are useful for the health of the human body. In 2016, ginger crop production tended to decline while demand continued to increase. Therefore, the breeding of ginger plants can be carried out using growth regulators auxin which can spur the growth and development ginger. The purpose of this study was to determine the optimal formulation against the growth of ginger in the vegetative phase. The study was conducted from February to April in Agricultural Land, Faculty of Agriculture, University of National Development